2017
DOI: 10.1136/heartjnl-2017-311340
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity evaluation in children with congenital heart disease

Abstract: Significant advances in the management of children with congenital heart disease (CHD) have resulted in marked improvements in survival and life expectancy. Thus, there is an increased emphasis on promoting physical activity to optimise healthy development and long-term cardiovascular health. Evaluation of physical activity levels as part of ongoing clinical care is recommended to facilitate physical activity counselling and/or exercise prescription. Physical activity is a complex health behaviour that is chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 39 publications
(27 reference statements)
1
18
0
Order By: Relevance
“…Furthermore, accurately assessing physical activity remains a challenging yet vital research endeavor in children with CHD. 8 The findings of this study underline the importance of objective and reliable measures in clinical pediatric settings as subjective reports in the form of questionnaires lack accuracy. Routine exercise testing is insightful in determining functional status but lacks the ability to determine habitual physical activity which is where commercially available wearables offer unique advantages.…”
Section: Original Articlesmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, accurately assessing physical activity remains a challenging yet vital research endeavor in children with CHD. 8 The findings of this study underline the importance of objective and reliable measures in clinical pediatric settings as subjective reports in the form of questionnaires lack accuracy. Routine exercise testing is insightful in determining functional status but lacks the ability to determine habitual physical activity which is where commercially available wearables offer unique advantages.…”
Section: Original Articlesmentioning
confidence: 77%
“…Whereas recalling physical activity in questionnaires lacks objectivity, more valid and reliable pedometers and accelerometers are often bulky, require technical expertise, are expensive, and not necessarily appealing to young children. 7,8 Furthermore, findings on childhood activity in CHD are conflicting. Smaller studies on children with complex CHD reported lower physical activity, [9][10][11] whereas more recent studies on a broad spectrum of CHD revealed these children to be of similar activity as healthy peers.…”
mentioning
confidence: 99%
“…In addition, at the end of the survey there was the possibility to provide ambiguities and questions directly as free text. Clearly, measuring PA by objective methods (i.e., accelerometry, pedometers, activity trackers) might be more precise (14). However, the objective assessment of PA in different domains can be challenging and requires complex strategies, which can hardly be applied in large patient populations.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Previous studies investigating PA in children with CHD showed rather conflicting results. While some authors reported of reduced PA, especially in complex CHD, others revealed similar PA-levels compared to healthy controls (12)(13)(14)(15)(16)(17)(18)(19)(20). Discrepancies of results might be explained by differences in study designs and PA assessment tools, and furthermore, common to all of these studies are relatively small patient numbers included.…”
Section: Introductionmentioning
confidence: 98%
“…Exercise improves cardiovascular function and exercise capacity ( 84 , 85 ) and psychosocial interventions, including eHealth, promote disease knowledge, compliance, and empowerment in these patients ( 86 , 87 ). For children with congenital heart disease, participation in both hospital and home-based cardiac physical activity programs is safe and feasible and improves QOL and exercise capacity ( 90 92 , 112 ). Finding proactive, engaging ways that promote physical activity and empowerment is important in promoting disease self-management as these teens transition into adulthood ( 5 ).…”
Section: Discussionmentioning
confidence: 99%